Analysis Of Alumina Particles Size And Shape Formation From Developed Planetary Ball Mill. Issue 5 (January 2020) - Ramasamy, D.; Mohanesen, K.; Maria, R; Samykano, M.; Kadirgama, K.; Rahman, M.M.
Abstract: This study emphasizes and the testing of alumina particles via a fabricated planetary ball mill. The fabrication of planetary ball mill work began with the design of the machine. Parts were fabricated separately then assembled. The jar and grinding media were made up of stainless steel as it as a higher strength property than Alumina powder. Testing and calibration are carried out through the response surface methodology utilizing the experimental results. Test is also executed to confirm the validity and the accuracy of the developed planetary ball mill. Based on the result obtain, the alumina powders have a particle size reduction of about 50% of the original particle size. Furthermore, the shape of the alumina particle changes from angular to irregular particle shape. It is apparent that the fabricated planetary ball mill able to grind the alumina powders and produce ultrafine particles by given period and parameter set. The fabricated ball mill able to function better than conventional ball mill. The planetary ball mill will be useful for the laboratory use purpose and production of ultrafine powder production. This ultrafine powder production can be used in application of powder metallurgy and advanced material research purposes.